'America's most precious resource': The future in American national identity and foreign policy. (September 2019) - Dunmire, Patricia L.
Highlights: U.S. national identity is rooted in a particular claim to the future. U.S. Cold War policy appropriated the future for the nation's security needs. particular discursive techniques underlying Modernization Theory's projection of the future. Abstract: This paper examines how a particular conception of American national identity, America as the "great nation of futurity, " was rhetorically deployed within an instance of post-World War II foreign policy discourse. I analyze projections of the future embedded within and disseminated through "modernization theory" and the rhetorical functions those projections served within the discourse. Modernization theory was a social scientific theory which provided a blueprint for restructuring post-colonial societies. I argue that the U.S.'s self-proclaimed identity as the nation of the future was an important aspect of modernization theory discourse and that this identity was used rhetorically to legitimate the nation's efforts to shape the future of postcolonial societies. Working within a Critical Discourse Analysis framework, I focus on two prominent modernization theory texts, Millikan & Rostow's A Proposal and Lerner's The Passing of Traditional Society. I analyze the discursive means through which the future of the newly decolonized societies was aligned with U.S. foreign policy interests and how an historically specific vision of the future was transformed into a universal, inevitable future. My analysis examines the space-times embedded in the texts, the relations and contrasts created between them, and how these contrasts served to legitimate, and, ultimately, universalize a projection of the future grounded in American interests, history, and identity.